Cultivation of Chlorella vulgaris in Membrane-Treated Industrial Distillery Wastewater: Growth and Wastewater Treatment - Li, Feng; Amenorfenyo, David Kwame; Zhang, Yulei; Zhang, Ning; Li, Changling; Huang, Xianghu (Frontiers in Environmental Science, 2021)
The alcohol industry discharges large quantities of wastewater, which is hazardous and has a considerable pollution potential. Cultivating microalgae in wastewater is an alternative way of overcoming the current high cost of microalgae cultivation and an environmentally friendly treatment method for industrial effluents. The study analyzed the growth and biochemical composition of Chlorella vulgaris cultivated in membrane-treated distillery wastewater (MTDW) and nutrients removal efficiency. The results showed biomass productivity of 0.04 g L−1 d−1 for MTDW with the contents of content of protein, carbohydrate, and lipid at 49.6 ± 1.4%, 26.1 ± 0.6%, and 10.4 ± 1.8%, respectively. The removal efficiencies of TN, TP, and COD were 80, 94, and 72.24% in MTDW, respectively. In addition, removal efficiencies of 100, 85.37, and 42.86% for Ca2+, Mg2+, and Mo2− were achieved, respectively. The study added to our growing knowledge on the cultivation of Chlorella with wastewater, suggesting that it was feasible to cultivate Chlorella with MTDW and represented an economical and environmentally friendly strategy for microalgae biomass production and reuse of wastewater resources.